1246. Prevalence of Hepatitis C Antibodies (Ab) in people at risk for HIV infection in Kentucky. (15th December 2022) - Soria, Jaime; Collins, Jana; Thacker, James; Hoven, Ardis; Thornton, Alice C
Abstract: Background: The Kentucky Income Reinvestment Program (KIRP) provides comprehensive early intervention services targeting those at the highest risk for HIV infection. The objective of this study was to evaluate the prevalence of Hepatitis C Antibodies (HCV Ab) in people at risk for HIV infections in Kentucky. Methods: A cross-sectional study was conducted using the KIRP Outreach database, including data from people at risk for HIV infections from January 2021 to March 2022. A screening tool was used to identify the people at risk. A Point-of-Care rapid test was used for the detection of HCV Ab. We compared the frequency of HCV Ab in People who inject drugs (PWID) versus people who denied the use of injected drugs. Study data were collected and managed using REDCap electronic data capture tools hosted at the University of Kentucky. Logistic Regression was performed, and the OR was reported. The statistical analyses were performed with Stata 17 (College Station, TX: Stata Corp LLC). Results: The analysis included data of 8, 225 people tested for Hepatitis C concomitant to screening for HIV; of them, 4, 203 (51.1%) were female, and the median age was 41 years old (Range: 17 – 76). No previous test for HCV Ab detection was reported in 3, 966 (48.2%). A total of 1, 180 (14.3%) tests were positive. HIV infection was detected in 14 (0.2%) people; of them 3 (21.5%) were in people with detectable HCV Ab. The prevalence of HCV Ab in PWID was 36.6%, and the prevalence in people who denied the use of injected drugs was 5.0% (p< 0.001). Most people with detectable HCV Ab (68.0%) were younger than 45. After being adjusted by age, HCV Ab was strongly associated with PWID (OR: 9.3; 95% CI 7.9 – 11.0; p< 0.001). Conclusion: The prevalence of the Hepatitis C virus in Kentucky remains higher, mainly in PWID; it was not associated with age. HCV/HIV Coinfection was identified in more than 20% of the Clients. Efforts to continue screening both HIV and HCV infections in PWID are necessary. Disclosures: All Authors : No reported disclosures.